The Rise of the Infrastructure State : How US-China Rivalry Shapes Politics and Place Worldwide (Bristol University Press, 2022)
Tensions between the US and China have escalated as both powers seek to draw countries into their respective political and economic orbits by financing and constructing infrastructure. Wide-ranging and even-handed, this book offers a fresh interpretation of the territorial logic of US-China rivalry, and explores what it means for countries across Eurasia, Africa, and Latin America. The chapters demonstrate that many countries navigate the global infrastructure boom by articulating novel spatial objectives and implementing political and economic reforms. By focusing on people and places worldwide, this book broadens perspectives on the US-China rivalry beyond bipolarity. It is an essential guide to 21st century politics.